2018
DOI: 10.1038/s42003-018-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Bats enhance their call identities to solve the cocktail party problem

Abstract: Echolocating bats need to solve the problem of signal jamming by conspecifics when they are in a group. However, while several mechanisms have been suggested, it remains unclear how bats avoid confusion between their own echoes and interfering sounds in a complex acoustic environment. Here, we fixed on-board microphones onto individual frequency-modulating bats flying in groups. We found that group members broaden the inter-individual differences in the terminal frequencies of pulses, thereby decreasing the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…The alternating short and long IPIs used by P. abramus and E. fuscus seem designed to probe into the entire scene, out to the longest delays in the room, while next looking closely to nearby objects to facilitate rapid guidance reactions. Miniopterus fuliginosus uses FM sounds similar to those recorded in flights here to hunt for flying insects (Hu et al, 2011), and they change the terminal frequency of their FM sweeps when flying in each other's company to avoid mutual jamming (Hase et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The alternating short and long IPIs used by P. abramus and E. fuscus seem designed to probe into the entire scene, out to the longest delays in the room, while next looking closely to nearby objects to facilitate rapid guidance reactions. Miniopterus fuliginosus uses FM sounds similar to those recorded in flights here to hunt for flying insects (Hu et al, 2011), and they change the terminal frequency of their FM sweeps when flying in each other's company to avoid mutual jamming (Hase et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there are few examples of bats that emit frequencymodulated (FM) echolocation calls to match conspecific calls. However, some FM bats clearly do respond to auditory feedback from conspecifics either by not producing echolocation calls [20] or by modifying call frequency in the presence of conspecifics [21][22][23][24] or ambient noise [25,26]. In contrast, bats that rely on constant frequency (CF) echolocation calls produce long duration sounds that are centered on a narrow frequency band, so it is relatively easy to determine if the frequency of an echolocation call emitted while the bat is at rest is the same or different than another individual.…”
Section: Saccopteryx Bilineatamentioning
confidence: 99%
“…These previous findings confirm that similarities in the FM pattern between sounds, and not the simple spectral pattern, cause jamming of echolocation at a higher order, such as target ranging, which utilizes the template of their own echolocation sounds Raver, 1996, 2000). In fact, during group flight, M. fuliginosus reportedly extend the frequency difference in individual TFs while increasing the intensity of emitted pulses and lengthening the pulse duration (Hase et al, 2018). Furthermore, Hase et al (2018) also demonstrated that the slight TF shift decreases the similarity between the dExp signals.…”
Section: Response Time Of the Tf Shiftmentioning
confidence: 93%
“…In fact, during group flight, M. fuliginosus reportedly extend the frequency difference in individual TFs while increasing the intensity of emitted pulses and lengthening the pulse duration (Hase et al, 2018). Furthermore, Hase et al (2018) also demonstrated that the slight TF shift decreases the similarity between the dExp signals. Taken together, echolocating bats could employ various strategies to avoid acoustic interference; they could improve the signal-to-noise ratio of their echoes by emitting louder and longer pulses, which is referred to as the Lombard effect.…”
Section: Response Time Of the Tf Shiftmentioning
confidence: 93%
See 1 more Smart Citation